2022
DOI: 10.3233/jad-220194
|View full text |Cite
|
Sign up to set email alerts
|

PSEN2 Mutation Spectrum and Novel Functionally Validated Mutations in Alzheimer’s Disease: Data from PUMCH Dementia Cohort

Abstract: Background: The established causative mutations in the APP, PSEN1, and PSEN2 can explain less than 1%,Alzheimer’s disease (AD) patients. Of the identified variants, the PSEN2 mutations are even less common. Objective: With the genetic study from the dementia cohort of Peking Union Medical College Hospital (PUMCH), we aim to illustrate the PSEN2 mutation spectrum and novel functionally validated mutations in Chinese AD patients. Methods: 702 AD participants, aged 30–85, were identified in PUMCH dementia cohort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The HEK293 cells transfected with PSEN2 N141S, I368F and M239T showed increased Aβ42 levels and ratio of Aβ42/Aβ40 relative to wild type PSEN2. The functional validation results of PSEN2 mutations were reported by our group previously 23 .…”
Section: Functional Validation Results Of Psen2 Mutationsmentioning
confidence: 79%
See 1 more Smart Citation
“…The HEK293 cells transfected with PSEN2 N141S, I368F and M239T showed increased Aβ42 levels and ratio of Aβ42/Aβ40 relative to wild type PSEN2. The functional validation results of PSEN2 mutations were reported by our group previously 23 .…”
Section: Functional Validation Results Of Psen2 Mutationsmentioning
confidence: 79%
“…Among 26 detected variants were novel discovered (among some variants were reported by our group previously). 22,23 16 patients (16/1277, 1.25%) have been identi ed carrying 11 causative APP variants, including 7 variants were novel; 16 patients (16/1277, 1.25%) have been identi ed carrying 13 causative PSEN1 variants, including 9 variants were novel; 14 patients (14/1277, 1.10%) have been identi ed carrying 12 causative PSEN2 variants, including 10 variants were novel.…”
Section: Resultsmentioning
confidence: 99%
“…PSEN2 is a critical component of ? -secretase, which is responsible for the proteolytic cleavage of the amyloid precursor protein (APP) and the formation of Aβ peptides and has recently been linked to AD ( Dong et al, 2022 ). Studies have found that AD-related PSEN2 dysregulation alters intracellular calcium signaling, resulting in the aggregation of Aβ to form brain plaques and cause neuronal cell death ( Pizzo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various APP mutations are linked to familial AD, for instance, the Swedish (K670_M671delinsNL), London (V717I), or Indiana (V717F) mutations that result in amplified production of amyloidogenic Aβ peptides or structural modifications which enhance the propensity of the peptides to aggregate (reviewed in 243 ). Additionally, variations in PSEN1 or PSEN2 , which encode for presenilin 1 (PS1) and 2 (PS2) that are part of the γ‐secretase complex, result in a dominant‐negative effect on γ‐secretase activity and alter the balance between Aβ 42 and Aβ 40 peptides 254,255 …”
Section: Ad Pathology: General Introduction and Isoform‐specific Cont...mentioning
confidence: 99%
“…Additionally, variations in PSEN1 or PSEN2 , which encode for presenilin 1 (PS1) and 2 (PS2) that are part of the γ‐secretase complex, result in a dominant‐negative effect on γ‐secretase activity and alter the balance between Aβ 42 and Aβ 40 peptides. 254 , 255 …”
Section: Ad Pathology: General Introduction and Isoform‐specific Cont...mentioning
confidence: 99%